Analisis Budidaya dan Pascapanen Melon Hidroponik di Akaruku Hydro Farm Berbasis Greenhouse - Yoesepa Pamela, Vega; Riany Eris, Fitria; Hana Dwiyanti, Norma; Putri, Nadilla; Nur Fitria, Aini (AGROTECH : JURNAL ILMIAH TEKNOLOGI PERTANIAN, 2025)
Hydroponic farming is increasingly popular as a modern, efficient, environmentally friendly, and sustainable agricultural solution, including in the cultivation of horticultural commodities such as melon (Cucumis melo L.). This study aims to analyze the stages of melon cultivation and post-harvest applied at Akaruku Hydro Farm, an agribusiness that develops a closed greenhouse hydroponic system in Cisauk District, Tangerang Regency, Banten. This study uses a qualitative descriptive method, with data collection techniques in the form of field observations and direct interviews with managers. The results of the study indicate that melon cultivation is carried out through the stages of sowing, planting, intensive care (embroidery, fertilization, pruning, pollination), harvesting when the fruit reaches optimal ripeness, and post-harvest which includes sorting, grading, packaging, labeling, and direct distribution to consumers. The application of modern agricultural technology in this practice not only produces high-quality commodities, but also makes a real contribution to food security and improving the local economy